Exploring biodiversity and ethnobotanical significance of Solanum species in Uzbekistan: unveiling the cultural wealth and ethnopharmacological uses - Gafforov, Yusufjon; Rašeta, Milena; Zafar, Muhammad; Makhkamov, Trobjon; Yarasheva, Manzura; Chen, Jia-Jia; Zhumagul, Moldir; Wang, Mengcen; Ghosh, Soumya; Abbasi, Arshad Mehmood; Yuldashev, Akramjon; Mamarakhimov, Oybek; et al. (Frontiers in Pharmacology, 2024)
Despite its millennial existence and empirical documentation, the ethnological knowledge of herbs is a more recent phenomenon. The knowledge of their historical uses as food, medicine, source of income and small-scale businesses, and the sociological impacts are threatened due to the slow ethnobotanical research drive. Species of the genus Solanum have long been extensively used in folk medicine to treat various illnesses of humans since the dawn of civilization.All data were systematically obtained from papers, monographs, and books written in Uzbek, Russian, and English through various scientific online databases, including Google, Google Scholar, PubMed, Scopus, Semantic Scholar, Science Direct, and Web of Science using specific keywords focused on eight Solanum species.